칸나에서 분리한 Cucumber mosaic virus의 특성 - 전용운(Yong Woon Jeon); 홍진성(Jin Sung Hong); 이상용(Sang Yong Lee); 류기현(Ki Hyun Ryu); 최장경(Jang Kyung Choi) (Sigmulbyeong yeon'gu, 2006)
An isolate of Cucumber mosaic virus(CMV), called as Can-CMV, was originally isolated from Canna generalis showing typical streak mosaic foliar symptoms, and its properties were investigated in this study. Whereas all known isolates of CMV could induce symptoms on their systemic hosts(four kinds of Nicotiana spp and a zucchini squash), Can-CMV induced no symptoms on its systemic hosts tested. Replication and movement of the virus on upper leaves as well as inoculated leaves-were confirmed by RT-PCR suggesting that Can-CMV could only infect systemically on N. benthamiana and N. glutinosa. Size of local lesions on the Can-CMV-inoculated leaves of Chenopodium amaranticolor was much smaller than that of Fny-CMV. Whereas Fny-CMV and LS-CMV could induce distinct necrotic local lesions on Vigna unguiculata 2 to 3 days postinoculation(dpi), chlorotic spots symptom was expressed by Can-CMV 4 to 5 dpi. Virus-specific 4 kinds of dsRNAs were isolated from leaves of N. benthamiana infected with Can-CMV, and these dsRNAs corresponded to the viral genomic RNAs and subgenomic RNAs and their patterns were indistinguishable to those of Fny-CMV and LS-CMV. By restriction mapping analysis of 950 bp of RT-PCR amplified products of coat protein gene of the virus as well as by serological analysis of gel diffusion test, Can-CMV belongs to a typical member of CMV subgroup IA. These results suggest that the Can-CMV isolated from C. generalis possesses unique pathological properties to understand further insight into the various interactions between virus and host. 전형적인 줄무늬 모자이크 증상을 나타낸 칸나로부터 Cucumber mosaic virus(CMV)의 한 계통(Can-CMV)을 분리하고, 특성을 조사하였다. Can-CMV는 대부분의 전신감염 기주에서 병징이 발현되지 않았고, 이들 기주의 접종엽 및 상엽에서 RT-PCR로 바이러스의 감염여부를 조사한 결과, N. benthamiana와 N. glutinosa에서만 바이러스가 검출되었으며, 다른 기주로부터는 확인되지 않았다. 한편 Chenopodium amaranticolor의 접종엽에 발현된 국부 괴사병반은 대조로 접종한 Fny-CMV나 LS-CMV에 의해서 형성된 병반보다 매우 작은 크기의 반점을 형성하는 특성을 보였다. 또한 Vigna unguiculata의 접종엽에는 Fny-CMV나 LS-CMV가 접종 2-3일 후에 뚜렷한 괴사병반을 형성하는데 반해서, Can-CMV는 접종 4-5일 후에 윤곽이 확실치 않은 퇴록병반을 형성하였다. Can-CMV에 감염된 N. benthamiana로부터 추출한 dsRNA는 4종의 밴드가 검출되었으며, 이들 분자의 크기 및 종수는 Fny-CMV나 LS-CMV와 차이를 나타내지 않았다. Can-CMV의 항원은 Fny-CMV의 항혈청에 대해서 한 종의 뚜렷한 침강선을 형성하였으며, Fny-CMV의 항원에 의해서 형성된 침강선과 융합하였고, LS-CMV의 침강선과는 분지선을 형성함으로서, 혈청학적으로 서브그룹 I에 속하는 계통으로 판단되었다. 또한 Can-CMV에 감염된 N. benthamiana로부터 RNA를 추출하여 CMV-specific 프라이머를 이용한 CMV-RNA3의 외피단백질 유전자를 포함하는 3'영역에 대해서 RT-PCR을 실시하였다. Can-CMV는 Fny-CMV나 LS-CMV와 마찬가지로 예상되었던 약 950bp크기의 cDNA가 증폭되었으며, 이 cDNA를 EcoRI으로 처리하였을 때에는 절단되지 않았고, MspI에서는 595bp 및 350bp의 절편으로 절단되었다. 이와 같은 결과는 Fny-CMV의 패턴과 일치하였으며, 이러한 결과로부터 Can-CMV가 서브그룹 IA에 속하는 계통으로 확인되었다. 이상과 같은 결과들로부터, Can-CMV는 앞으로 바이러스와 기주의 다양한 상호관계를 이해하는데 있어서 중요한 병원학적 성질을 가지고 있는 것으로 생각되었다.